Hybrid sol–gel coatings for corrosion mitigation: a critical review - Figueira, Rita Bacelar (2020)
The corrosion process is a major source of metallic material degradation, particularly in aggressive environments, such as marine ones. Corrosion progression affects the service life of a given metallic structure, which may end in structural failure, leakage, product loss and environmental pollution linked to large financial costs. According to NACE, the annual cost of corrosion worldwide was estimated, in 2016, to be around 3%–4% of the world’s gross domestic product. Therefore, the use of methodologies for corrosion mitigation are extremely important. The approaches used can be passive or active. A passive approach is preventive and may be achieved by emplacing a barrier layer, such as a coating that hinders the contact of the metallic substrate with the aggressive environment. An active approach is generally employed when the corrosion is set in. That seeks to reduce the corrosion rate when the protective barrier is already damaged and the aggressive species (i.e., corrosive agents) are in contact with the metallic substrate. In this case, this is more a remediation methodology than a preventive action, such as the use of coatings. The sol-gel synthesis process, over the past few decades, gained remarkable importance in diverse areas of application. Sol–gel allows the combination of inorganic and organic materials in a single-phase and has led to the development of organic–inorganic hybrid (OIH) coatings for several applications, including for corrosion mitigation. This manuscript succinctly reviews the fundamentals of sol–gel concepts and the parameters that influence the processing techniques. The state-of-the-art of the OIH sol–gel coatings reported in the last few years for corrosion protection, are also assessed. Lastly, a brief perspective on the limitations, standing challenges and future perspectives of the field are critically discussed.